Development of Android-Based Learning Media for High School Students in Indonesia: A Systematic Review of Literature - Yohanis Ndapa Deda; Hermina Disnawati; Otaget Daniel; Rooselyna Ekawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to comprehensively examine research on developing android-based learning media(ABLM) in Indonesia from 2015 to 2022. The research method used is the SLR to explore 32 articles from the accreted journals Sinta 1 and Sinta 2 by the Kemristekdikti RI with the keyword